Online Health Promotion about Anemia Towards Adolescent Females and It’s Effectiveness - Gusti Ayu Marhaeni; Ni Gusti Kompiang Sriasih; Ni Nyoman Astika Dewi; Ni Ketut Nuratni; Ni Nyoman Budiani; Ni Wayan Armini (Jurnal Bidan Cerdas, 2026)
Background: Anemia poses greater risk in females, contributing to stunting. Despite reliance on online platforms, limited research  investigated their impact on adolescents' knowledge, attitudes, and practices toward anemia prevention. This study aimed to evaluate the effectiveness of online health promotion towards the knowledge, attitude, and practices of adolescent females in preventing anemia. Methods: This experimental study employed a pretest-posttest control group design. The intervention group received an online health promotion and module, while the control group received a leaflet. The sample was 100 female students from two senior high schools, selected through proportional stratified random sampling. The instrument used questionnaires validated by all items have r count > r table (0.195), and a reliability test using Cronbach’s Alpha obtained > 0.7, showing reliable instrument. The analysis utilized a non-parametric test Wilcoxon test, to understand the effectiveness with effect size, and the Mann-Whitney test to compare differences between groups. Results: Statistical tests revealed significant effectiveness and differences (p<0.05), within the large effect size of 0.92–0.96. The magnitude was evident in intervention group; 90% respondents showed good knowledge, 92% positive attitudes and practices, compared to the control group, showed 64% attitudes, 62% practices, and 62% knowledge. The results imply that online health education with module-based health is effective in empowering adolescents about anemia. Conclusion: The findings underscore the effectiveness of online health promotion. Schools can adopt this approach as policy to promote sustainable and healthy practicess for anemia prevention. Further research should provide refinement, involve larger and more diverse population with socioeconomic analysis.